Pembangunan Berkelanjutan Berbasis Kearifan Lokal Sektor Perikanan - M. Adli Abdullah (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: There are two important things become a global issue until then, namely sustainable development and local wisdom. In Aceh there are patterns of local wisdom that hukom Laot custom has been known since the kingdom. The pattern is believed to have a positive impact in saving huge potential fisheries in Aceh today, but it's also a picture that there is the spirit of local communities in Aceh in the use of fisheries resources sustainably. Especially in the local wisdom that there are rules and customary courts, and has a territory with a clear resources. Sustainable Development Based on Local Wisdom in Fishery Sector